Management practices affect tenderness of strip loin but not knuckle steaks from fed mature cows - Neill, S.; Marston, T.T.; Daniel, M.J.; Higgins, James J.; Unruh, John A.; Dikeman, Michael E.; Hunt, Melvin C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
Approximately 16% of cattle slaughtered in the United States are cows. When these cows are removed from the herd, they are typically in thin condition. Steaks from these cows are considered tougher than those from young steers and heifers but could potentially be improved with alternative management practices, such as high concentrate feeding. Feeding high-concentrate diets, implanting, and feeding β-agonists prior to harvest have been shown to improve performance and carcass meat yields. However, the effect on steak tenderness of feeding Zilmax (zilpaterol hydrochloride; Intervet Inc., Millsboro, DE) to mature cows is unknown. Therefore, the objective of this study was to determine the effects of concentrate feeding, implanting, and feeding Zilmax on tenderness of strip loin and knuckle steaks from cull cows fed for 70 days.
Keywords: Beef; Cattle; Steak tenderness